Pokhran and beyond India's nuclear behaviour - Kapur, Ashok (New Delhi ; Oxford : Oxford University Press, 2001)
Examines India's nuclear policy in the context of the challenges of war, terrorism, the country's domestic politics, its regional environment, and its national interests and values. Tracing the origins and trajectory of India's nuclear diplomacy, this book generates interest among Indian, Pakistani and Western academic and policy circles.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Nuclear weapons -- Government policy -- India; India -- Foreign relations; India -- Military policy